Pengembangan Buku Panduan Konseling Kognitif Behavioral Teknik Cognitive Restructuring Untuk Meningkatkan Resiliensi Akademik Siswa SMA - Serafina Elasa Budiono; Kadek Suranata; Dewi Arum Widhayanti Metra Putri (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study aims to develop and test the validity and effectiveness of cognitive behavioral counseling guidance books with cognitive restructuring techniques in increasing academic resilience of high school students, this research was carried out based on the 4D development procedure by Thiagarajan. This study involved 5 experts in the field of Counseling Guidance, who evaluated the counseling manual theoretically, and involved 33 students as respondents to the counseling guidance books effectiveness trial. Data analysis related to the validity and effectiveness of the guidebook was carried out using the calculation of the Content Validity Ratio, Content Validity Index, and t-test. The results of the CVR analysis showed that all questionnaire item statements were accepted and the CVI calculation results were 0.94 in the very good category. The results of the effectiveness test of the guidebook that was carried out on 33 students in 11th grade with a one group pre-test and post-test design, showed that the use of the cognitive behavioral counseling guidebook with cognitive restructuring techniques was effective in increasing the academic resilience of high school students.